Identifying How Any Interface Elements Are Created in The Gamemaker Engine - jibran prawiko; normalisa; pradana atmadiputra (Liaison Journal of Engineering, 2023)
A GUI, whether well or badly designed, is one of the most important requirements for any video game. The role of a GUI is to present the player with their in-game character’s current status, whether it’s the number of ammunitions of a weapon, the current active quest, or the player’s current location within the game’s map. Creating GUI elements should be one of the first guides that are taught after a GameMaker tutorial provides a guide on creating a camera object. The creation process of a GUI element can be divided into two parts; its positioning and functionality. In theory, simplifying the development process, in this case the algorithm, for creating GUI elements is possible, mainly by categorizing every GUI element based on what they are presenting to the player. Developers could then create the same algorithm for every element that falls in one category, thus simplifying the development process. Keywords: GUI elements, game development, simplification, categorization.